“Sovereign Chișinău or abyss with NATO” Moscow and the Moldovan EU referendum 2024 - Nico Lamminparras (Bulletin of "Carol I" National Defense University)
The Moldovan EU referendum in October 2024 proved a page-turner; the Yes votes won by a thin margin. Russia was the first to condemn the process. In this article, I apply discourse analysis to scrutinize the language of the Russian MFA through the utterance of its spokesperson, Maria Zakharova. Intermittently, securitization schemes are employed. My aim is to divulge Moscow’s standpoint on Moldova via the maneuvers that Zakharova takes advantage of in her official statements.